Complex therapy of accommodation disturbances in children. Review - E. Yu. Markova; A. V. Matveev; L. V. Uljshina; L. V. Venidiktova (Oftalʹmologiâ, 2014)
Different accommodation disturbances in children and adolescents are described. Chronic excess accommodative effort repre- sents stable hypertonus of ciliary muscle due to permanent near visual activity. Comparative complex medical therapy of accommoda- tion disturbances in children is described.